Specific sequence of arrival promotes coexistence via spatial niche pre‐emption by the weak competitor. (21st May 2022) - Fragata, Inês; Costa‐Pereira, Raul; Kozak, Mariya; Majer, Agnieszka; Godoy, Oscar; Magalhães, Sara
Abstract: Historical contingency, such as the order of species arrival, can modify competitive outcomes via niche modification or pre‐emption. However, how these mechanisms ultimately modify stabilising niche and average fitness differences remains largely unknown. By experimentally assembling two congeneric spider mite species feeding on tomato plants during two generations, we show that order of arrival affects species' competitive ability and changes the outcome of competition. Contrary to expectations, order of arrival did not cause positive frequency dependent priority effects. Instead, coexistence was predicted when the inferior competitor ( Tetranychus urticae ) arrived first. In that case, T . urticae colonised the preferred feeding stratum (leaves) of T . evansi leading to spatial niche pre‐emption, which equalised fitness and reduced niche differences, driving community assembly to a close‐to‐neutrality scenario. Our study demonstrates how the order of species arrival and the spatial context of competitive interactions may jointly determine whether species can coexist. Abstract : Here we show that when the weaker competitor arrives first it takes the preferred resources from the stronger competitor. Such niche preemption leads to coexistence between two herbivores species ( Tetranychus urticae and Tetranychus evansi ). This result challenges the commonly though inhibitory role of niche pre‐emption on species coexistence.